Effects of combined l-carnitine supplementation and moderate-intensity exercise on body composition, metabolic and oxidative stress markers, bone parameters and muscular performance in overweight and obese individuals - Samsudin, Norsuriani (2023)
The effects of 12 weeks of combined L-carnitine supplementation and moderateintensity exercise on body composition, metabolic and oxidative stress markers, bone parameters and muscular performance in overweight and obese individuals were determined. Sixty-eight participants aged 29.03 ± 6.02 years old were divided into control (C), L-carnitine supplement (S), exercise (E), combined L-carnitine and exercise (SE) groups. Participants in supplement groups consumed 1 tablet of 1000mg L-carnitine daily. Participants in exercise groups performed 30 minutes of brisk walking (50% HRmax) and continued with 10 to 20 minutes of interval training per session, 3 times per week. Mean energy intake was higher than their mean energy expenditure. The percentages of carbohydrate, protein and fat intakes were significantly higher than recommended nutrient intake (RNI) values. After 12 weeks of intervention, there were significant reduction (p< 0.05) in body weight, body mass index, fat percentage, fat mass, and increase (p< 0.05) in fat free mass (FFM) in S, E and SE groups. Regarding metabolic markers, waist to hip ratio, blood glucose, triglycerides, low-density lipoprotein, and total cholesterol, SE group expressed the highest reduction (p< 0.05) compared to C group. All groups showed enhancement (p< 0.05) in both radial and tibial speed of sound of dominant and non-dominant arms and legs within the groups except for C group. There were significant greater (p< 0.05) extension and flexion peak torque and average power in both legs and arms at 60o.s-1 and 300o.s-1 in S, E and SE groups compared to C group and SE group was expressed the greatest value. In comparison with C groups, all groups showed greater values of serum ALP (p< 0.05) and total calcium (p < 0.05), but significantly lower value of serum 1CTP (p< 0.05). Malondialdehyde (MDA) and reactive oxygen species (ROS) values significantly reduced in all groups (p< 0.05) except for C group. Meanwhile for antioxidant markers, serum catalase (CAT) and superoxide dismutase (SOD), all groups displayed greater increment (p< 0.05) compared to C group, and SE group demonstrated the highest increment. In terms of interleukin-6, S and SE groups also showed higher decrement (p< 0.05), meanwhile E group showed higher increment compared to C group, and the greatest decrement (p< 0.05) was observed in SE group. The toxicity test explained that L-carnitine supplement are safe to be consumed in 12 weeks. Generally, combinations of L-carnitine supplement with brisk walking and interval exercise for 12 weeks elicit beneficial effects to improve overall parameters in overweight and obese individuals.